Significance and roles of the public and private sectors and the community in the touristy process of war relics - Yoji Ishii (Journal of Rural Tourism, 2025)
Purpose - This paper argues for the significance and role of the public sector, private sector, and local communities in the tourism development process of war relics. Methodology - The approach is conceptual and argumentative, focusing on the analysis of stakeholder roles and the interrelationships required to support sustainable and meaningful tourism centered on war relics. Findings - The study finds that the public sector needs to take the lead in establishing a long-term vision for regional development. The private sector plays a key role in providing funding diversity and improving service quality. In addition, local community participation is essential for building consensus on the interpretation of war relics and for coordinating stakeholder efforts in a balanced and effective way. Originality - This paper offers an integrated perspective that emphasizes the importance of aligning public leadership, private sector engagement, and community consensus in the development of war-related tourism, with a focus on peace-building and sustainable regional progress.